Action as a form of temporal unity: on Anscombe's Intention. Issue 5 (December 2015) - Lavin, Douglas
Abstract: The aim of this paper is to display an alternative to the familiar decompositional approach in action theory, one that resists the demand for an explanation of action in non-agential terms, while not simply treating the notion of intentional agency as an unexplained primitive. On this Anscombean alternative, action is not a worldly event with certain psychological causes, but a distinctive form of material process, one that is not simply caused by an exercise of reason but is itself a productive exercise of reason. I argue that to comprehend the proposed alternative requires an account of the temporality of events in general. An event does not simply have a position in time, but is itself temporally structured. With the inner temporality of events in view, the Anscombean conception of action as a specifically self-conscious form of temporal unity is made available for critical reflection.